Analisis Prinsip Konservasi Momentum Dalam Tabrakan Listrik dan Tidak Elastis - Tulus Hati Berkat Zega; Sini Siska Kristiani Lase (CV. SINAR HOWUHOWU, 2024)
This study discusses the principle of momentum conservation in elastic and inelastic collisions through a comprehensive literature review. Momentum conservation is a fundamental concept in physics, stating that the total momentum of a closed system remains constant if no external forces act upon it. In an elastic collision, both the total momentum and kinetic energy of the system are conserved before and after the collision. Conversely, in an inelastic collision, only the total momentum is conserved, while some kinetic energy is lost and converted into other forms of energy, such as heat or deformation. This article explores experiments and theories supporting this principle, as well as applications in various fields of science and technology. The results of the literature analysis indicate that a deep understanding of momentum conservation in elastic and inelastic collisions can aid technological advancements in the automotive, aerospace, and safety sectors